The Effect of Financial Literacy, Lifestyle, and E-Money Use on the Consumptive Behavior of Generation Z As K-Pop Fans in the Greater Bandung Area, With Self-Control as a Moderating Factor - Adinda Setiawati; Eka Yulianti (LP2M IAIN Palopo, 2026)
Gen Z in particular may be influenced by the K-Pop craze in Indonesia to engage in more materialistic spending habits. Lifestyles that prioritize consumption, the convenience of online payment systems, and individuals' differing degrees of financial knowledge all contribute to this. With self-control serving as a moderating variable, this research seeks to examine the impact of financial literacy, lifestyle, and e-money use on the consumption behavior of Generation Z K-Pop fans in Greater Bandung. A quantitative approach is used in the study. Through the use of purposive sampling, 202 K-Pop fans from Generation Z in Greater Bandung were surveyed to gather primary data. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to do the data analysis. The findings showed that there was a negative and insignificant relationship between financial literacy and consumption habits. Lifestyle and e-money use, on the other hand, dramatically and favorably impacted consumption habits. A lack of self-control does not mitigate the effect of lifestyle and financial literacy on consumption behavior, according to the moderation variable test. The impact of electronic money on spending may be mitigated, nevertheless, via exercise of restraint.